Grape, wine and pomace anthocyanins: winemaking biochemical transformations, application and potential benefits - Katarina Delić; Danijel D. Milinčić; Mirjana B. Pešić; Steva Steva Lević; Viktor A. Nedović; Anne-Laure Gancel; Michael Jourdes; Pierre-Louis Teissedre (OENO One)
Anthocyanins are polyphenols found in red grapes, wines and their by-products. This scientific paper reviews their physiological significance in grape tissues, the biochemical transformations they undergo during winemaking and wine aging, their potential application in the food industry, and the health benefits associated with them. The paper sheds light on the factors influencing their extraction, stability and composition in wines, and explores their applications in various food products and the possibility of sustainable winemaking using pomace. The paper focuses on the broad impact of anthocyanins on product quality and consumer preferences, and highlights potential preventive and therapeutic applications for human health conditions. Overall, this comprehensive overview provides valuable insights into the multifaceted roles of anthocyanins, paving the way to future research on the application of anthocyanin in agriculture, food science and medicine.